Titik Balik Ekonomi Indonesia Pasca Kemerdekaan: Perspektif Materialisme Historis - Moch. Dimas Galuh Mahardika (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
Meja Bundar Conference held in Den Haag at 1949 was an achievement in the diplomatic process of the Indonesian nation to show its existence as an independent and politically sovereign country. However, on the economic aspect, the results of the conference did not favor the Indonesian government. The Dutch debt burden was imposed on the Indonesian government as a reciprocity for the Dutch recognition of Indonesia's political sovereignty. As a country that is young and unstablished economically yet, of course the requirements are very burdensome. Therefore, the government is looking for an effective way out to meet these requirements. One of the paths taken is to nationalize foreign companies that were still operating at the time. The decision also considered suitable to build the foundation of the national economy and dismantle the colonial economic system that had previously been formed. So to achieve this goal, political elites and society, especially laborer must be participated. This article, written using historical methods, aims to elaborate on the colaboration between political elites and laborer an effort to nationalize foreign companies in the 1950’s from a historical materialism perspective.